Women's Self-Concept Has a Dual Role in Career and Household - Eka Susilawati; Noerma Kurnia Fajarwati; Dedeh Fardiah; Neng Putri (Journal of Law Science, 2024)
Self-concept is a person's image of knowing themselves, which is a combination of beliefs about their physical, psychological, social, emotional, aspirations and achievements. Women with dual roles in career and household have different self-concepts according to the meaning they receive from their environment. The research method uses a qualitative approach. The research results concluded that a career woman means a woman who has a job and is financially independent, whether working for someone else or having her own business, who has a self-concept as a smart woman and a modern woman. Career women even try to prove that they are capable of carrying out their duties well and being successful in their careers. Meanwhile, women's roles in the family are divided into three, namely: as wife, mother and child, all of which require duties and responsibilities in accordance with their roles. The position of women in the family and society needs to be maintained and improved so that they can make the greatest contribution to national development by paying attention to their nature and dignity. As a wife, a woman plays a role in serving her husband, fulfilling her obligations towards her husband because behind a great man (husband) there is a great woman (wife) too. A girl child has an equal position with a boy so parents should provide the broadest possible education